Physiological and Epigenetic Features of Yoyo Dieting and Weight Control - Contreras, Raian E.; Schriever, Sonja C.; Pfluger, Paul T. (Frontiers in Genetics, 2019)
Overweight and obesity have become a worldwide epidemic affecting more than 1.9 billion adults and 340 million children. Efforts to curb this global health burden by developing effective long-term non-surgical weight loss interventions continue to fail due to weight regain after weight loss. This weight cycling, often referred to as Yoyo-dieting, is driven by physiological counter-regulatory mechanisms that aim at preserving energy, i.e. decreased energy expenditure, increased energy intake, and impaired brain-periphery communication. Models based on genetically determined set points explained some of the weight control mechanisms, but exact molecular underpinnings remained elusive. Today, gene-environment interactions begin to emerge as likely drivers for the obesogenic memory effect associated with weight cycling. Here, epigenetic mechanisms, including histone modifications, DNA methylation and chromatin remodelling, appear as most likely mechanisms that underpin long-lasting deleterious adaptations or an imprinted obesogenic memory that prevents weight loss maintenance. In this review, we interrogate the role of epigenetic mechanisms for the control and maintenance of body weight. We first summarize human and murine studies on the Yoyo dieting phenomenon and describe physiological adaptations associated with weight loss and weight re-gain. Next, we highlight the specific roles of homeostatic and hedonic food intake control centres in the CNS, and summarize current evidence linking epigenetic mechanisms with CNS reward behavior, obesity and weight cycling. Last, we describe major opportunities and challenges associated with studying epigenetic mechanisms in the CNS with its highly heterogenous cell populations, and provide a summary of recent technological advances that will help to delineate whether an obese memory is based upon epigenetic mechanisms.